1993
DOI: 10.1007/bf00000871
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of greenhouse gases between soils and the atmosphere in a temperate forest following a simulated hurricane blowdown

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Springer is collaborating with JSTOR to digitize, preserve and extend access to Biogeochemistry.http://www.jstor.org Abstract. Fluxes of nitrous oxide (N20), carbon dioxide (CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 23 publications
6
41
0
2
Order By: Relevance
“…Addition of temperature to the model increased predictability by 5% (r 2 =0.84). This agrees with ®eld work at the Harvard Forest (Bowden et al, 1993), where a multiple linear regression of CH 4¯u xes to temperature and moisture showed that these two factors together strongly predicted CH 4 uptake (r 2 =0.80).…”
Section: Methanesupporting
confidence: 87%
See 2 more Smart Citations
“…Addition of temperature to the model increased predictability by 5% (r 2 =0.84). This agrees with ®eld work at the Harvard Forest (Bowden et al, 1993), where a multiple linear regression of CH 4¯u xes to temperature and moisture showed that these two factors together strongly predicted CH 4 uptake (r 2 =0.80).…”
Section: Methanesupporting
confidence: 87%
“…Crill, 1991;Fernandez et al, 1993;Yavitt et al, 1995), including work at the Harvard Forest (Bowden et al, 1993;Peterjohn et al, 1994). The Q 10 values (from 158C to 258C, at 50% of soil moisture capacity) of 2.03 for the forest¯oor and 2.39 for the mineral soil are within the range of 1.4 to 3.8 reported for a variety of temperate forest soils (Schlesinger, 1977;Dorr and Munnich, 1987;Crill, 1991;Kicklighter et al, 1994).…”
Section: Carbon Dioxidementioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the CTE treatments did not reflect additional groundwater responses to past hurricanes because there were no increases in dissolved organic nitrogen, ammonium, or potassium concentrations associated with canopy opening or debris deposition (McDowell and Liptzin, 2014). Similarly, in the Harvard LTER blowdown study there were small, if any, changes to soil nutrients, including nitrogen (Bowden et al, 1993). Therefore, nitrate appears to be the most responsive nutrient to hurricane disturbance in the LEF, and its increase is generated by the opening of the canopy occurring simultaneously with the deposition of nutrient-rich debris on the forest floor.…”
Section: Microclimatic Attributes (Light Moisture Debris)mentioning
confidence: 97%
“…Previous research (Walker et al, , 1996aZimmerman et al, 1996; identified canopy loss and the accumulation of debris on the forest floor as key factors that govern responses during secondary succession. Although the CTE is the first experimental study of hurricane effects conducted in a tropical forest, there was an experiment in temperate forest at the Harvard Forest LTER site in northeastern USA, where whole trees were pulled down in a single plot to simulate conditions of a previous major hurricane (Bowden et al, 1993;Carlton and Bazzaz, 1998;Cooper-Ellis et al, 1999;Barker Plotkin et al, 2013). The main effects observed in the temperate experiment were reduced basal area of trees due to the physical application of the manipulation, increased light levels, and establishment of pioneer tree species in areas of soil disturbance caused by uprooting (Carlton and Bazzaz, 1998;Cooper-Ellis et al, 1999;Barker Plotkin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%